Control Evaluation Information System Savings - Eddy Sutedjo; Yulianty Yulianty; Iwan Kurniawan (CommIT (Communication and Information Technology) Journal, 2011)
The purpose of this research is to evaluate the control of information system savings in the banking and to identify the weaknesses and problem happened in those saving systems. Research method used are book studies by collecting data and information needed and field studies by interview, observation, questioner, and checklist using COBIT method as a standard to assess the information system control of the company. The expected result about the evaluation result that show in the problem happened and recommendation given as the evaluation report and to give a view about the control done by the company. Conclusion took from this research that this banking company has met standards although some weaknesses still exists in the system.Index Terms - Control Information System, Savings